Psychotherapies for depression: a network meta‐analysis covering efficacy, acceptability and long‐term outcomes of all main treatment types - Cuijpers, Pim (World Psychiatry, 2021)
The effects of psychotherapies for depression have been examined in several hundreds of randomized trials, but no recent network meta‐analysis (NMA) has integrated the results of these studies. We conducted an NMA of trials comparing cognitive behavioural, interpersonal, psychodynamic, problem‐solving, behavioural activation, life‐review and “third wave” therapies and non‐directive supportive counseling with each other and with care‐as‐usual, waiting list and pill placebo control conditions. Response (50% reduction in symptoms) was the primary outcome, but we also assessed remission, standardized mean difference, and acceptability (all‐cause dropout rate). Random‐effects pairwise and network meta‐analyses were conducted on 331 randomized trials with 34,285 patients. All therapies were more efficacious than care‐as‐usual and waiting list control conditions, and all therapies – except non‐directive supportive counseling and psychodynamic therapy – were more efficacious than pill placebo. Standardized mean differences compared with care‐as‐usual ranged from –0.81 for life‐review therapy to –0.32 for non‐directive supportive counseling. Individual psychotherapies did not differ significantly from each other, with the only exception of non‐directive supportive counseling, which was less efficacious than all other therapies. The results were similar when only studies with low risk of bias were included. Most therapies still had significant effects at 12‐month follow‐up compared to care‐as‐usual, and problem‐solving therapy was found to have a somewhat higher long‐term efficacy than some other therapies. No consistent differences in acceptability were found. Our conclusion is that the most important types of psychotherapy are efficacious and acceptable in the acute treatment of adult depression, with few significant differences between them. Patient preference and availability of each treatment type may play a larger role in the choice between types of psychotherapy, although it is possible that a more detailed characterization of patients with a diagnosis of depression may lead to a more precise matching between individual patients and individual psychotherapies.